Peranan Kepemimpinan Camat Dalam Implementasi Program Pemberdayaan Masyarakat Di Kecamatan Damau Kabupaten Kepulauan Talaud - Maarebia, Marta Firsa; Lengkong, Florence Daicy Jetty (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: The purpose of this research is to find out leadership role sub-district implementation people empowerment program Damau sub-district Talaud. Data sources/ informant 15 people taken from government element sub-districts, government work units government element village unsure (BPD, LPM) and the citizens. Document collected by engineering interview. Data analysis used interactive model techniques. The result of this research are: (1) leadership role in sub-district coÃ¶rdination implementation and supervision of people empowerment program Damau sub-district Talaud in doing so good. (2) national community empowerment program PNPM MP independent national programs is in a policy framework as the basic reference and the implementation of poverty eradication programs dna-based pemberdayaan society. With the existence of this community empowerment program public life in Damau sub-district Talaud peace, can say and life more economic growth. (3) based on conclusion this research and leadership roles can be expressed not only the need for the implementation of community empowerment programs but also SDM people become purpose and objective pemberdayaan to watch. Think of this then Research results suggested: sub-district coÃ¶rdination leadership role in implementation and supervision of people empowerment program needs to be improved in sub-district Damau, Talaud. Keywords: leadership, community empowermen.